1975
DOI: 10.1073/pnas.72.4.1226
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence for an additional function of phage T4 gene 32 protein: interaction with ligase.

Abstract: Gene 32 of bacteriophage T4 is essential for DNA replication, recombination, and repair. In an attempt to clarify the role of the corresponding gene product, we have looked for mutations that specifically inactivate one but not all of its functions and for compensating suppressor mutations in other genes. Here we describe a gene 32 ts mutant that does not produce progeny, but in contrast to (6,(9)(10)(11). It is produced in large amounts after T4 infection and is limiting for phage production (12). This cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1976
1976
2003
2003

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Highly specific interactions also occur between DNA unwinding proteins and DNA polymerases (29,37,38,44,47). Indirect evidence suggests a further interaction between the T4 DNA unwinding protein and the T4 DNA ligase (40) and perhaps with other as yet unidentified T4 proteins (34). a See Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Highly specific interactions also occur between DNA unwinding proteins and DNA polymerases (29,37,38,44,47). Indirect evidence suggests a further interaction between the T4 DNA unwinding protein and the T4 DNA ligase (40) and perhaps with other as yet unidentified T4 proteins (34). a See Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…All base pair substitution pathways are affected. Possible physiological interactions between gene 32 and rII mutations (40) have been eliminated as causes of altered revertant frequencies of rII mutations in gene 32 ts backgrounds.…”
mentioning
confidence: 99%
“…The DNA arrest phenotype of gene 59 mutants had suggested that gp59 is not required during origin initiation but is required for recombination-dependent DNA replication (see below). The 5Ј-to-3Ј exonuclease function of host DNA polymerase I can substitute for defective T4 RNase H (427) and E. coli ligase can substitute for T4 ligase, if the T4 rII genes are mutated (59,159,504,580,776 (Table 2), because these genes are important for recombination-dependent DNA replication and repair of broken forks (see below). Since DNA is constantly assaulted by intrinsic and extrinsic damaging agents, DNA replication and recombination are tightly correlated and should not be considered in isolation.…”
Section: Dna Replication Proteinsmentioning
confidence: 99%
“…Although in E. coli it has not yet been possible to replication (23) encoded membrane proteins, namely the products of the only confer a replication defect but also an accomrIlA and rlIB genes (27). defect (Xgx) that results in blue colonies on X-Gal…”
Section: Resultsmentioning
confidence: 99%